Erring on the Side of Theresa Schiavo: Reflections of the Special Guardian ad Litem - Wolfson, Jay (The Hastings Center report, 2005)
THE SCHIAVO CASE Four commentators discuss what made it so difficult, why it was more complex than most realized, and what we should do differently.